Media Multitasking Is Associated With Higher Body Mass Index in Pre-adolescent Children - Lopez, Richard B.; Brand, John; Gilbert-Diamond, Diane (Frontiers in Psychology, 2019)
Obesity rates among children have climbed dramatically in the past two decades, a time period in which children also experienced greater exposure to portable media devices and smartphones. In the present study, we provide evidence of a potential link between media multitasking—using and switching between unrelated forms of digital media—and risk for obesity, as indexed by body mass index (BMI). Specifically, we recruited 179 pre-adolescent children (aged 9-11 years, 88 females) to participate in a study in which we assessed their media multitasking tendencies, as well as BMI. Controlling for the influence of genetic factors that contribute to obesity and other covariates, we found a positive association between the frequency of children’s MMT behaviors and age- and sex- standardized BMI z-scores, b = 1.05, p = .012. These findings are consistent with other recent work showing similar patterns of covariation between MMT and risk for obesity in young adults. The present work can also inform future work in this realm, such as the design of longitudinal studies that prospectively measure children’s MMT behaviors and body composition to begin to identify directionality in the association.